2007
DOI: 10.1007/s11414-007-9074-2
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Adherence To Guidelines Improves Opioid Dependent Patients’ First Year Outcomes

Abstract: Clinical practice guidelines for opioid substitution treatment (OST) for opioid dependence recommend that patients receive at least 60 mg daily methadone and have access to a broad array of psychosocial services. However, there is still wide variation in clinical practice in OST clinics. In real-world settings, patients could receive lower methadone doses and less psychosocial care because they require less intensive care for recovery; alternatively, barriers to delivery of guideline concordant care could limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Guidelines to reduce practice variability are associated with improved outcomes (4547). The American College of Critical Care Medicine developed guidelines for analgesia/sedation in critically ill adults in 1995, updated in 2002 (48, 49), but similar guidelines are not available for children.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines to reduce practice variability are associated with improved outcomes (4547). The American College of Critical Care Medicine developed guidelines for analgesia/sedation in critically ill adults in 1995, updated in 2002 (48, 49), but similar guidelines are not available for children.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that MMT is effective 19 if delivered under best practices guidelines. 1,20,21 Although MMT has been proven to be effective for some, it is well documented that a significant proportion of patients are not attracted into or do not respond to this therapy. 22,23 Many nonresponders relapse into the use of illicit street drugs and/or continue injecting illicit opiates even during methadone treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The MOST study evaluated the effect of compliance with opioid substitution treatment guidelines, and its methods are described in detail elsewhere (Humphreys et al, 2008;Trafton et al, 2007). The opioid substitution programs operated by the U.S. Department of Veterans Affairs (VA) were sent a one-page screening survey requesting information about two practices recommended by guidelines: dispensing at least 60 mg methadone per day and providing extensive psychosocial services.…”
Section: Methodsmentioning
confidence: 99%
“…The Multisite Opiate Substitution Treatment (MOST) study found that after 1 year, new clients of methadone treatment programs that were highly concordant with treatment guidelines were more abstinent, had better psychiatric status, and were more satisfied than those who entered less-concordant programs (Humphreys, Trafton, & Oliva, 2008;Trafton, Humphreys, Harris, & Oliva, 2007). We now consider the economic impact of guideline concordance.…”
Section: Introductionmentioning
confidence: 99%